Can silylenes rival transition metal systems in bond-strengthening pi-back donation? a computational investigation - Pal, Amrita; Vanka, Kumar (Chemical Communications, 2014)
Full quantum chemical calculations with density functional theory (DFT) show that bond-strengthening back-donation to a pi-diborene, recently discovered for transition metal systems (Braunschweig and co-workers, Nat. Chem., 2013, 5, 115-121), would be just as favored for Main Group silylene complexes. This result not only shows the range and applicability of the bond-strengthening back-bonding interaction, but also showcases the capacity of silylene complexes to do new chemistry, such as the cooperative activation of carbon monoxide and carbon dioxide.